2008
DOI: 10.3892/or.19.3.737
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 transcription factor decoy reduces the TGF-β1-induced cell growth in scleroderma fibroblasts through inhibition of cyclin E

Abstract: The transforming growth factor-ß (TGF-ß) signaling pathway plays a key role in the abnormal accumulation of type I and III collagen of scleroderma. Activator protein-1 (AP-1) is a key regulatory protein in TGF-ß1-induced type I collagen synthesis. However, it is largely unknown whether AP-1 is involved in the cell proliferation of fibroblasts in scleroderma. In this study, we investigated the effects of the AP-1 oligo-deoxynucleotide (ODN) decoy on TGF-ß1induced cell growth in scleroderma fibroblasts. To inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(34 reference statements)
0
4
0
2
Order By: Relevance
“…These six miRNAs are hsamiR-206, hsa-miR-133a, hsa-miR-125b, hsa-miR-140-5p, hsa-miR-23b and hsa-let-7 g, and they regulate hundreds of target genes. Some of the target genes are involved in SSc pathogenesis, particularly the targets of hsa-miR-206, which regulates about 516 target genes, including 15 genes [21][22][23][24][25][26]. The upregulation of these targets in SSc skin lesions and blood, and in cell or mouse On the whole, the target genes of the differentially expressed miRNAs involved in SSc pathology play important roles in many processes including the cell cycle, cell proliferation, differentiation, apoptosis, cell signaling, inflammation, fibrosis and SSc development.…”
Section: Discussionmentioning
confidence: 99%
“…These six miRNAs are hsamiR-206, hsa-miR-133a, hsa-miR-125b, hsa-miR-140-5p, hsa-miR-23b and hsa-let-7 g, and they regulate hundreds of target genes. Some of the target genes are involved in SSc pathogenesis, particularly the targets of hsa-miR-206, which regulates about 516 target genes, including 15 genes [21][22][23][24][25][26]. The upregulation of these targets in SSc skin lesions and blood, and in cell or mouse On the whole, the target genes of the differentially expressed miRNAs involved in SSc pathology play important roles in many processes including the cell cycle, cell proliferation, differentiation, apoptosis, cell signaling, inflammation, fibrosis and SSc development.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor decoy oligonucleotides have been used to modulate gene expression in vitro and in vivo . Decoys for NF-kB (29,30,55–58), STAT3 (59,60), p53 (61), E2F (62,63) and AP-1(64) have been previously proposed. Our decoys are mimics of a G4-DNA structure that can be formed in NHE of the human KRAS promoter.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major mechanisms by which TGF-β induces fibrosis is stimulating fibroblast proliferation and activation. TGF-β has been shown to stimulate the proliferation and activation of fibroblasts originating from different organ systems [136141] and ROS/RNS play critical role in this process [98, 103]. Cucoranu et al reported that TGF-β treatment stimulated the expression of Nox4 and alpha smooth muscle actin (α-SMA), a myofibroblast marker, in primary human cardiac fibroblasts while knockdown of Nox4 by siRNA reduced TGF-β-stimulated production of ROS and α-SMA mRNA expression, suggesting that ROS mediate TGF-β-induced differentiation of cardiac fibroblasts to myofibroblasts [98].…”
Section: Ros and Tgf-β’s Fibrogenesismentioning
confidence: 99%